2010
DOI: 10.2217/nnm.10.52
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and Cytotoxicity of Zinc Oxide and Titanium Dioxide in HEp-2 Cells

Abstract: Aims: The rapidly growing industrial and medical use of nanomaterials, especially zinc oxide and titanium dioxide, has led to growing concerns about their toxicity. Accordingly, the intrinsic genotoxic and cytotoxic potential of these nanoparticles have been evaluated. Materials & methods: Using a HEp-2 cell line, cytotoxicity was tested along with mitochondrial activity and neutral red uptake assays. The genotoxic potential was determined using the Comet and the cytokinesis-blocked micronucleus assays. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 63 publications
3
57
1
4
Order By: Relevance
“…Nevertheless, the in vitro results obtained using the comet assay in this study produced positive responses independent of the cell type used. This occurred when this nanomaterial was tested using different mammalian cell line models such as primary mouse embryo fibroblasts (Yang et al, 2009), human epidermal (A431) cells (Sharma et al, 2009), human negroid cervix carcinoma Hep-2 cells (Osman et al, 2010), human bronchial epithelial cells BEAS-2B (Ng et al, 2011), human epidermal keratinocytes (HEK) (Sharma et al, 2011a), human liver HepG2 cells (Sharma et al, 2011b), human hepatocytes (L02), and human embryonic kidney (HEK293) cells (Guan et al, 2012). On the other hand, Kumari et al (2011) studied the cytotoxicity and genotoxicity of ZnO NPs (<100 nm) on root cells of A. cepa.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the in vitro results obtained using the comet assay in this study produced positive responses independent of the cell type used. This occurred when this nanomaterial was tested using different mammalian cell line models such as primary mouse embryo fibroblasts (Yang et al, 2009), human epidermal (A431) cells (Sharma et al, 2009), human negroid cervix carcinoma Hep-2 cells (Osman et al, 2010), human bronchial epithelial cells BEAS-2B (Ng et al, 2011), human epidermal keratinocytes (HEK) (Sharma et al, 2011a), human liver HepG2 cells (Sharma et al, 2011b), human hepatocytes (L02), and human embryonic kidney (HEK293) cells (Guan et al, 2012). On the other hand, Kumari et al (2011) studied the cytotoxicity and genotoxicity of ZnO NPs (<100 nm) on root cells of A. cepa.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc nanoparticles in the range 10-100 μg/mL were used for 24-48 h on HEp-2 cells. The observed results from the study demonstrated that the zinc oxide nanoparticles were toxic for the cells causing DNA damage and reduction in cell viability [216]. Another study focused on the assessment of in vivo toxicity of zinc nanoparticles at 14-20 μg/mL for 12 h to determine the effects of treatment on cell viability, DNA damage, ROS production and apoptosis [217].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…60 ZnO NPs (,100 nm) induced genotoxicity in HEp-2 human cervix carcinoma cells, using the Comet assay and the cytokinesis-blocked micronucleus assay. 61 Genotoxicity was associated with increased tyrosine phosphorylation.…”
Section: Genotoxicity Studies In Vivo and In Vitro In Vivo Studiesmentioning
confidence: 99%